Retatrutide - revolutionary recently developed GLP agonist - literature review - Patrycja Brzozowska; Agata Frańczuk; Bianka Nowińska; Aleksandra Makłowicz; Karolina Palacz; Iwona Lenartowicz (Nicolaus Copernicus University in Toruń, 2024)
Obesity - defined by excessive amount of fat tissue - is becoming more and more serious health problem among our population and affecting a growing number of people [1]. It is crucial in treatment to encourage and adjust patients to increased physical activity and decreased food consumption. However, it its much easier said than done, resulting in lowered motivation and many failed attempts at patients which makes it more difficult to engage in weight loss process. Holistic approach from medical team is crucial. More drugs are becoming approved in treatment of obesity - which is a big step for patients having a high body mass index (BMI) for whom diet and exercise might not be enough in order to lose weight. One of these drugs is retatrutide which appears to be a game-changer amongst other medications. It is revolutionary since it is a "triple G" agonist - it affects glucagon-like peptide (GLP) receptors, glucose-dependent insulotropic polypeptide (GIP) receptors and glucagon (GCG) receptors. It is a first substance of already available weight loss drugs that affects all three mentioned receptors - eg. semaglutide is a GLP receptor agonist and recently developed tirzepatide is a GLP and GIP receptors agonist. It could lead to revolutionizing weight loss treatments industry, making it even more successful and efficient. The aim of our study is to describe this new drug, its' mechanism of action and discuss possible benefits versus adverse effects.